Perancangan Aplikasi Pengenalan dan Pembelajaran Pertanian Milenial Hidroponik Berbasis Android Flutter & Dart Dengan Metode RAD - Recky Arianto (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Hydroponics is an alternative farming system from conventional agriculture, this system is quite easy to implement because it does not need to use a large area of land, meaning that this system can be applied to a narrow planting area, such as a house yard or rooftop. take advantage of the empty area around their residence, especially the Blok G3 Alam Parung Housing, Ciseeng - Bogor Regency, therefore this study will design an android-based application as an educational medium for the introduction of hydroponic systems using the RAD method. The purpose of designing this application is to design an application as an educational medium for information about hydroponic agriculture based on Android and make this application easy to use in learning hydroponic farming, the results of this study indicate that this application 30% of respondents agreed if this application educates them , and 10% stated strongly agree and 60% expressed doubt, and also 30% of respondents thought that this application makes it very easy for them to learn, besides this application there is also material in the form of video learning materials, while the other 30% think agree, 30% stated undecided and 10% disagree.